Development of MMC gamma detectors for nuclear analysis - Bates, C.; Pies, Christian; Kempf, Sebastian; Gastaldo, Loredana; Fleischmann, Andreas; Enss, Christian; Friedrich, S. (Journal of low temperature physics, 2014)
Non-destructive assay (NDA) of nuclear materials would benefit from gamma detectors with improved energy resolution in cases where line overlap in current Ge detectors limits NDA accuracy. We are developing metallic magnetic calorimeter gamma-detectors for this purpose by electroplating $$\sim $$∼150 $$\upmu $$μm thick Au absorbers into microfabricated molds on top of Au:Er sensors. Initial tests under non-optimized conditions show an energy resolution of $$\sim $$∼200 eV FWHM at 60 keV. Monte Carlo simulations illustrate that this resolution is starting to be sufficient for direct detection of $$^{242}$$242Pu in plutonium separated from spent nuclear fuel.